Physiological and psychological stress in pregnant women with quiescent inflammatory bowel disease: A pilot study using salivary biomarkers. Issue 4 (4th March 2020) - Khil, Jennifer; Picardo, Sherman; Seow, Cynthia H.; Leung, Yvette; Metcalfe, Amy; Afshar, Elnaz E.; Sharifi, Nastaran; Campbell, Tavis; Letourneau, Nicole; Dewey, Deborah; Giesbrecht, Gerald F.; ,
Abstract: Background: Pregnant women with inflammatory bowel disease (IBD) are more likely than the general pregnant population to experience adverse maternofetal outcomes, especially if the disease is active at the time of conception and during pregnancy. Elevated stress is often seen in patients with chronic diseases and could account for these outcomes. Salivary cortisol and alpha‐amylase (sAA) are novel biomarkers of stress, reflecting the hypothalamic‐pituitary‐adrenal (HPA) axis and sympathetic nervous system, respectively. Our aim in this pilot study was to assess stress differences between pregnant women with inactive IBD and matched controls using psychometric questionnaires and salivary biomarker measures. Methods: Thirteen pregnant women with quiescent IBD (6 Crohn's disease, 7 ulcerative colitis) were matched (1:3) to 39 expectant mothers without IBD by parity and gestational age. Participants completed several psychometric questionnaires assessing stress, and salivary cortisol and sAA were collected as objective biomarkers of stress during pregnancy. Results: Pregnant women with quiescent IBD did not demonstrate significant differences on any psychometric measures of stress or salivary biomarker measures when compared with controls (all P  > 0.05). Pregnant women with quiescent IBD demonstrated similar cortisol and sAA awakening responses (both P  > 0.05) and total levels of cortisol and sAA production (both P  > 0.05) when compared with controls. Conclusions: Pregnant women with well‐controlled IBD do not experience demonstrable differences in psychological stress or dysregulation of salivary stress biomarkers when compared with non‐IBD controls. The effect of chronic disease may be evaluated in future studies by including a comparative group of pregnant women with active IBD. Abstract : Stress differences between expectant mothers with and without quiescent inflammatory bowel disease (IBD) were assessed using psychometric questionnaires and salivary biomarker measures. Pregnant women with well‐controlled IBD did not demonstrate significant differences in psychological stress or dysregulation of salivary stress biomarkers when compared with non‐IBD controls. The effect of chronic disease may be evaluated in future studies by including a comparison group of pregnant women with active IBD.